Towards a Principal-Agent Based Typology of Risks in Public-Private Partnerships - De Palma, Andre; Leruth, Luc.; Prunier, Guillaume (Washington, D.C. : International Monetary Fund, 2009)
There is a strong economic rationale for close cooperation between the public and private sectors. This has resulted in a significant increase in the demand for the provision of public services through instruments combining public and private money such as public-private partnerships (PPPs or P3s). We describe these arrangements and explore how they can be analyzed using standard tools in economics (incentives and principal-agent theory). We discuss the implications of our approach in terms of identifying risks that are often overlooked before turining to the optimal risk-sharing between the public and private partners, in particular with respect to information asymmetries in risk perceptions. This allows us to propose a typology of the risks associated with PPPs, where both internal risks (the risks associated with the contract) and external risks (those associated with the project) are considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States